Kepemimpinan Hashim Ibn ‘Abd Manaf Terhadap Bangsa Quraysh - Muhammad Nur Shiddiq (Universitas Islam Negeri Alauddin Makassar, 2023)
This article discusses the figure of Hashim ibn ‘Abd Manaf as the leader of the Quraish nation. He is the ancestor of Rasulullah Saw, who was the first to open a new trade route outside the city of Mecca twice a year. By using literature research, this article finds historical information that the success of the Quraish nation was pioneered by one of the traders, who later became known as a leader and trading figure among them. Hashim ibn ‘Abd Manaf's character can be seen from his expertise in seeing opportunities to change the trade route (silk route) in the northern region, which was often disrupted by wars between Rome and PersIa. With his diplomatic techniques, Hashim ibn ‘Abd Manaf succeeded in proposing a change in the trade route from the north to the south that crossed Mecca. This path became known as the rihlat al-shita wa al-sayf path and was immortalized in the Koran with the revelation of the Quraish letter. The findings of this article provide an illustration that the success of a nation can be built through the nation's ability to seize opportunities. Hashim ibn 'Abd Manaf was a leader who was able to see these opportunities and apply them to leading the Quraish nation.